2007
DOI: 10.1103/physrevd.75.084028
|View full text |Cite
|
Sign up to set email alerts
|

Brane cosmic string compactification in Brans-Dicke theory

Abstract: We investigate an alternative compactification of extra dimensions using local cosmic string in the Brans-Dicke gravity framework. In the context of dynamical systems it is possible to show that there exist a stable field configuration for the Einstein-Brans-Dicke equations. We explore the analogies between this particular model and the Randall-Sundrum scenario. DOI: 10.1103/PhysRevD.75.084028 PACS numbers: 11.25.ÿw, 04.50.+h, 12.60.Fr The search of an alternative compactification of extra dimensions is a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…An important characteristic about braneworld models in the BD theory is that, generally, the scalar field depends only on the large extra dimensions [10]. This type of dependence is indeed useful since the projected EBD equations on the brane leads to important subtle modifications but still resembles the Einstein's equations [11].…”
Section: Generalized Sum Rulesmentioning
confidence: 99%
See 1 more Smart Citation
“…An important characteristic about braneworld models in the BD theory is that, generally, the scalar field depends only on the large extra dimensions [10]. This type of dependence is indeed useful since the projected EBD equations on the brane leads to important subtle modifications but still resembles the Einstein's equations [11].…”
Section: Generalized Sum Rulesmentioning
confidence: 99%
“…Let us particularize our analysis to braneworld models inspired in one of those previously found in this framework. In the models proposed in [10], all the bulk-brane structure was generated by using local and global cosmic string as sources. The final scenario is composed by 4-branes…”
Section: )mentioning
confidence: 99%
“…In Ref. [10] a local cosmic string generating the braneworld model was studied, while in Ref. [11] a braneworld was investigated with the aid of a global cosmic string.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to investigate whether the no-go theorem is valid in the Brans-Dicke case, we have to adequate our previous approach to this case [13,14].…”
Section: B the Brans-dicke Casementioning
confidence: 99%
“…On the other hand, as stated, since the equivalence is only valid for specific cases, a full treatment of both cases is necessary. It is interesting to note that the consistency conditions were already incorporated in the context of f (R) [12] and BD gravities [13,14], in these works it was shown that both f (R) and BD theories are suitable to accommodate consistent scenarios without negative tension branes.…”
Section: Introductionmentioning
confidence: 99%